Technology Adoption Models - An Empirical Comparative Analysis for LMS Technology in Higher Education - T C, Kavitha; Maddodi, Chetana (International Journal of Engineering and Technology, 2018)
The rapid technological advancement is changing the landscape of higher education. The efficacy of technology has spurred higher educational institutions to transform their educational structures and modes of knowledge dissemination from process-focused to student-focused.Â Â Â  Higher educational institutions are adopting new information and communication technological (ICT) tools to enhance teaching-learning process and student engagement.Â  One such ICT tool which blends technology in the classrooms into educational experiences is the learning management system (LMS). The LMS usage by the higher education institutions facilitates the students for â€œanytime and anywhere accessâ€ to the contents. In this context this paper examines the acceptance of learning management system as a technological tool among students. And, examines the critical factors that effects the behavioral intentions of students towards LMS usage and factors influencing the actual usage of the LMS. The study also focuses on comparing the threemodelsof technology adoption, TAM, revised version of TAM and C-TAM-TPB.Â  The comparative analysis of three models discloses that perceived ease of use and perceived behavioral control being an important exogenous variable in understanding the behavioral intention and actual usage. The study was conducted among the first year business management students of private deemed university.Â Â